2022
DOI: 10.1002/er.7706
|View full text |Cite
|
Sign up to set email alerts
|

An ultrahigh‐energy density and wide potential window aqueous electrolyte supercapacitor built by polypyrrole/aniline 2‐sulfonic acid modified carbon felt electrode

Abstract: Summary In this study, excellent performance and wide operating voltage are obtained with an aqueous electrolyte. Aqueous electrolytes are attracted more attention than other electrolytes (such as organic solvents, ionic liquids) in supercapacitor applications because of their safety, low cost, nontoxicity. Polypyrrole (PPy), aniline 2‐sulfonic acid (ASA) modified electrodes are hydrothermal synthesized on carbon felt (CFt) for supercapacitor applications. We investigate the presence of the concentration of AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 125 publications
(209 reference statements)
0
13
0
Order By: Relevance
“…In most of the supercapacitor studies using carbonbased materials as a current collector in the literature, the operating voltage range is wide. [63][64][65] The cyclic stability of CFt/Fe-PANI/LGB(3 mM) was tested by successive GCD for 2400 cycles at current density of 13.3 A g À 1 (40 mA.cm À 2 ). PANI chains caused PANI to exhibit poor cycling stability due to shrinkage and swelling during electrochemical process.…”
Section: Chemistryselect Electrochemical Performance Of Supercapacito...mentioning
confidence: 99%
“…In most of the supercapacitor studies using carbonbased materials as a current collector in the literature, the operating voltage range is wide. [63][64][65] The cyclic stability of CFt/Fe-PANI/LGB(3 mM) was tested by successive GCD for 2400 cycles at current density of 13.3 A g À 1 (40 mA.cm À 2 ). PANI chains caused PANI to exhibit poor cycling stability due to shrinkage and swelling during electrochemical process.…”
Section: Chemistryselect Electrochemical Performance Of Supercapacito...mentioning
confidence: 99%
“…In the literature, it has been observed that the potential range is expanded in supercapacitor studies where carbonbased active materials and current collectors are used. 11,46,47 Nyquist plots of Ba doped PEDOT:PSS, Sn doped PEDOT: PSS, Ba:Sn doped PEDOT:PSS and undoped PEDOT:PSS electrodes were shown in Fig. 9(f).…”
Section: Electrochemical Performance Of Electrodesmentioning
confidence: 99%
“…In this area, conductive polymers, carbon-based materials, transition metal oxide, transition metal nitrides, transition mixed metal oxide and other materials are widely used. [4][5][6][7][8][9][10][11] Conducting polymers are more preferred in SCs devices because of their high electrical conductivity and electrochemical stability. Another important advantage of using an organic polymer as an electrode in SCs compared to carbon-based electrodes is that it makes it possible to manufacture transparent devices.…”
Section: Introductionmentioning
confidence: 99%
“…Electric double-layer capacitors, pseudocapacitors, and hybrid capacitors with both can be classified based on their energy storage system (2). In pseudocapacitors, a redox process occurs to store the charge, while in EDLCs, charges are electrostatically accumulated at the electrode/electrolyte interface (3). In hybrid supercapacitors, these two events co-occur on the electrode surface.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when the conductive polymer structure is doped with large anions, since the polymer is immobile in the matrix, small electrolyte cations are involved in the charging/discharging process without large volume changes. Thus, the cyclic stability of the polymers is improved (3). The strong contact between the functional groups of the dye molecules as a counterion and the PANI improves capacitance performance (12).…”
Section: Introductionmentioning
confidence: 99%